Evaluation System for Teacher Performance with Data Analysis, Result and Conclusion Using Open Source Technology - Paresh R. Rathod; P.M. Dolia (International Journal of Data Structure Studies, 2024)
Evaluation in general is an element of everyday culture. People are judged and evaluated in most areas of society as to what their value is to their institution. Teacher performance evaluation has been a continuous process. Change in teacher performance evaluations is a recent educational phenomenon in education. Evaluation system for teacher performance is developed using open source tools and technologies like PHP PDO evaluation system using seven different criteria like students’ evaluation by teachers, self evaluation by teachers, teacher evaluation by colleague, third party teacher evaluation by higher position, teacher evaluation by documents, teacher evaluation by students and teacher evaluation by parents to identify teacher performance evaluation. Evaluation system is online, different principals of schools are using this system and identified their teacher performance evaluation. Using this tool, institute or organization can identify what has been achieved, what needs to be improved and what should be developed.
Keywords: Performance; Teacher; analysis; conclusion; evaluation system; result